Service Quality as A Measurement of Customer Satisfaction of Indonesian Sharia Bank Using Important Performance Analysis Method - Budi Santoso; Tutik Alawiyah (Universitas Pendidikan Ganesha, 2021)
Consumer satisfaction can be a realization that the company expects to provide some form of service to its customers. Consumer satisfaction with services depends on the comparison between the needs of consumers before using the service with the results perceived by consumers. This study aims to analyze the quality of service that determines customers’ satisfaction. This type of research is quantitative. The population in this study were all customers of the Indonesian Islamic bank Situbondo. The sample used is 100 respondents. The types of data used are primary data and secondary data. The method uses the IPA (Important Performance Analysis) method to analyze to find out which service attributes need to be improved and maintained. The results of this study indicate that the results of the analysis of the IPA method have 3 service attributes that are included in Quadrant I, which means that there are 3 service attributes that must be prioritized to be improved, because the performance of service attributes is less satisfying to customers and is considered important by customers. So this result implied that Indonesian Sharia Bank must always pay attention to and improves all attributes that are considered lacking and still need improvement, so as to increase customer satisfaction in terms of service.